2014
DOI: 10.1002/chem.201404396
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for the Preparation of Thioantimonates Based on the Concept of Weak Acids and Corresponding Strong Bases

Abstract: By following a new synthetic approach, which is based on the in situ formation of a basic medium by the reaction between the strong base Sb(V)S4 (3-) and the weak acid H2 O, it was possible to prepare three layered thioantimonate(III) compounds of composition [TM(2,2'-bipyridine)3 ][Sb6 S10 ] (TM=Ni, Fe) and [Ni(4,4'-dimethyl-2,2'-bipyridine)3 ][Sb6 S10 ] under hydrothermal conditions featuring two different thioantimonate(III) network topologies. The antimony source, Na3 SbS4 ⋅ 9 H2 O, undergoes several decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…Most of these compounds were synthesized by solvothermal reactions using the elements as reactands, which is a disadvantage for several reasons. Recently, we have found that many such compounds are more easily available if simple metal salts such as, for example, Schlippe's salt (Na 3 SbS 4 Á9H 2 O) or NaSbS 3 are used as starting materials (Anderer et al, 2014(Anderer et al, , 2016Danker et al, 2020). The major advantage of this approach is the fact that different SbS x species are present in solution, which in some cases allows the preparation of thioantimonates already at room temperature.…”
Section: Chemical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these compounds were synthesized by solvothermal reactions using the elements as reactands, which is a disadvantage for several reasons. Recently, we have found that many such compounds are more easily available if simple metal salts such as, for example, Schlippe's salt (Na 3 SbS 4 Á9H 2 O) or NaSbS 3 are used as starting materials (Anderer et al, 2014(Anderer et al, , 2016Danker et al, 2020). The major advantage of this approach is the fact that different SbS x species are present in solution, which in some cases allows the preparation of thioantimonates already at room temperature.…”
Section: Chemical Contextmentioning
confidence: 99%
“…The major advantage of this approach is the fact that different SbS x species are present in solution, which in some cases allows the preparation of thioantimonates already at room temperature. The reactions in solution are complex, but it has been found that Schlippe's salt is unstable and forms different species such as, for example, [SbS 3 (Anderer et al, 2014;Long et al, 1970;Rammelsberg, 1841;Planer-Friedrich & Wilson, 2012;Planer-Friedrich & Scheinost, 2011;Mosselmans et al, 2000).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The chalcogenidometalate family encompasses ab road spectrum of compounds with amultitude of applications stemming from their tunable optoelectronic and semiconducting properties; [1][2][3][4][5][6] al arge subgroupof this family are the chalcogenidotetrelates. [7,8] Ac haracteristic feature of tin chalcogenide chemistry is the reoccurrence of topologies, such as the [Sn 3 E 4 ] defect-ah eterocubane unit (DC, E = S, Se), most often aggregated through further Ea toms into frameworks [9][10][11] -or the adamantane-like [Sn 4 E 6 ]t in sesquichalcogenide unit (AD), which is also knownf or af ew tin telluride clusters (E = Te ).…”
Section: Introductionmentioning
confidence: 99%
“…Organic hybrid thioantimonates(III) (aepH 2 )[Sb 6 S 10 ] (aep = 1‐(2‐aminoethyl)‐piperazine),40 [(dach)(dachH 2 )][Sb 6 S 10 ] (dach = trans‐1, 2‐diaminocyclohexane),41 and (Ph 4 P) 2 [Sb 6 S 10 ] 42 contain the 1D chain‐like [Sb 6 S 10 ] 2– anion, which is constructed by SbS 3 and SbS 4 units. The 2D [Sb 6 S 10 ] 2– anion with Sb 2 S 2 , Sb 4 S 4 , and Sb 7 S 7 hetero‐rings in [ TM (bipy) 3 ][Sb 6 S 10 ] ( TM = Ni, Fe; bipy = 2, 2′‐bipyridine) is composed of SbS 3 and SbS 4 units 43…”
Section: Resultsmentioning
confidence: 99%